2010
DOI: 10.1016/j.jpdc.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation algorithms for virtualized service hosting platforms

Abstract: 13/01/15 meb. Accepted version, Ok to add

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(96 citation statements)
references
References 47 publications
0
96
0
Order By: Relevance
“…Following our argumentation, we further investigated the listed publications with respect to the evaluation of QoS aspects and summarize the results in Table 1. [21] dynamic no spare capacity Rolia2005 [22] dynamic yes spare capacity Bichler2006 [23] dynamic no not explicitly considered Cherkasova2006 [41] dynamic yes spare capacity Stillwell2010 [19] static no not explicitly considered Xu2010 [66] static no not explicitly considered Speitkamp2010 [14] dynamic no quantiles of historical service demands Feller2011 [43] dynamic no not explicitly considered Gao2013 [67] static no not explicitly considered At first, Table 1 distinguishes between static and dynamic workload. If the optimization problem implicates a time dimension for service capacity demands, we consider the approach to be dynamic, following the classification by [43].…”
Section: Service and Component Capacity Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Following our argumentation, we further investigated the listed publications with respect to the evaluation of QoS aspects and summarize the results in Table 1. [21] dynamic no spare capacity Rolia2005 [22] dynamic yes spare capacity Bichler2006 [23] dynamic no not explicitly considered Cherkasova2006 [41] dynamic yes spare capacity Stillwell2010 [19] static no not explicitly considered Xu2010 [66] static no not explicitly considered Speitkamp2010 [14] dynamic no quantiles of historical service demands Feller2011 [43] dynamic no not explicitly considered Gao2013 [67] static no not explicitly considered At first, Table 1 distinguishes between static and dynamic workload. If the optimization problem implicates a time dimension for service capacity demands, we consider the approach to be dynamic, following the classification by [43].…”
Section: Service and Component Capacity Managementmentioning
confidence: 99%
“…In their allocation problem, they maximize the minimum yield over all services to consider performance and fairness. However, actual response time estimations were not quantified [19]. In the same year, Speitkamp et al state that workloads which exceed the available capacity may lead to increased response times, but it remains unclear to which extent response times are affected [14].…”
Section: Service and Component Capacity Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…For practical vector packing in 1-dimensions, it is well known that FF and Best-fit (BF) [7] and their off-line counterparts, FFD and BFD, strike the best balance between their time complexity and performance in terms of number of bins. Stillwell et al [14] showed FFDSum to be a good choice for resource allocation algorithms for virtualized service platforms. Generalizing BF and BFD for vector packing can be done in many ways.…”
Section: Related Workmentioning
confidence: 99%